2017
DOI: 10.24193/tras.52e.9
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Should Public Corporations Be Consolidated? Considering the Effects on Public Deficit and Debt in Spanish Municipalities

Abstract: The consolidation perimeter of the public sector is the most important line between the micro and macro systems of government accounting. This paper focuses on the public sector boundary and assesses the potential impact on key reported figures -such as the 'Maastricht' deficit and debt ratios -that would result from moving public corporations inside the perimeter of the consolidated general government sector, public corporations that currently lie outside the general government sector. After examining 90 Span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The employment of such institutions enables the municipalities to circumvent the constraints imposed on them to curb their deficit and indebtedness, and the debts thus generated can remain hidden from the central government. In their study, De Vicente Lama et al [8] demonstrated that the method of taking Spanish municipal businesses into account could have a heavy impact on municipalities' compliance with the financial regulations. They found that the businesses in municipal ownership are capable of converting the budget deficit into an off-budget item, thus making the local government fiscal situation unhealthy.…”
Section: Central/general Factors (1) Liberalization and Deregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The employment of such institutions enables the municipalities to circumvent the constraints imposed on them to curb their deficit and indebtedness, and the debts thus generated can remain hidden from the central government. In their study, De Vicente Lama et al [8] demonstrated that the method of taking Spanish municipal businesses into account could have a heavy impact on municipalities' compliance with the financial regulations. They found that the businesses in municipal ownership are capable of converting the budget deficit into an off-budget item, thus making the local government fiscal situation unhealthy.…”
Section: Central/general Factors (1) Liberalization and Deregulationmentioning
confidence: 99%
“…According to the literature, the level of subnational indebtedness may be influenced by the ideology of the current governing party and the stability of the power of municipal leaders. Based on Spanish data, Vicente Lama et al [8] found significant correlation between the ideology of the governing party and the extent of indebtedness. Other country studies, for example Seitz [17], who analysed the determinants of subnational deficits in Germany, did not find any significant impact on indebtedness from the political composition of local governments.…”
Section: ) Local Policymentioning
confidence: 99%